اعتماد البخاري قرينة السماع في رد وقبول الروايات (مختارات من أبواب الطهارة) - Hakima Ahmed Hafidi; Siham Omara; Abd Errahman Mashagba (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
Hadith scholars agree on the fact that a narrator hearing a saying from his shaikh is strong evidence of the sanad connection. They also agree that this condition has the highest degree of endurance in proving the connection between the narrator and those who narrated from him. That’s why critic Imams have caringly and carefully used it in judging whether a narration is continuous or disconnected. And Imam al-Bukhari was among those who stipulated hearing as a condition for authenticity, whether in his collective Sahih or his other books like “the Great History” (Attarikh Alkabir)  or what was reported from him by his student Imam  Al-Tirmidhi in his Al-Ilal Alkabir  book, as the latter often asked his Shaikh about his opinion on narrations and he answered him with acceptance or denial based on lack of evidence of hearing between the narrator and his Shaikh, which emphasises the importance of this matter and its research. This is why this research’s objective is to highlight this issue according to Imam Al-Bukhari through what his student Al-Tirmidhi reported from him in the chapters on purification (Attahara), in his two books Al-Ilal Al-Kabir and Al-Jami. Three methods are used in this paper: The inductive method was adopted when collecting the examples mentioned in the study, and the analytical and critical approaches when studying the sayings. Three important conclusions can be mentioned. First, denying or proving that a narrator heard a saying with his own ears is one of the most prominent clues that indicate the connection of the narration chain or its interruption. Second, that Imam al-Bukhari relied on this presumption in accepting and refuting the narrations in most examples of these chapters. Thirdly, that sometimes Imam al-Bukhari does not rely on the presumption of hearing alone in the authentification of the narration, but rather supports it with other evidence.